Advanced control and energy management of microgrids - Tan, Kuan Tak (2014)
The liberalization of electricity market and the integration of advanced information and communication technology into the power industry have attracted widespread adoption on the microgrid concept. The microgrid concept offers consumers increased reliability and quality in service provided by utility companies. The reduction in global emissions and energy losses also makes the microgrid a promising alternative to traditional power distribution systems. Furthermore, over the last decades, efficient and reliable communication and control technologies coupled with an increase in smarter electrical facilities such as electric vehicles and smart meters have resulted in an increasing number of consumers participating in demand response management (DRM). The current research works are also focused on achieving a smarter grid through demand side management (DSM), increasing energy reserves and improving service quality. However, the design of a microgrid architecture that provides an efficient operation and control still poses a challenging problem.